Parents weekend : a novel - Finlay, Alex (Minotaur Books, 2025)
"In the glow of their children's exciting first year of college at a small private school in Northern California, five families plan on a night of dinner and cocktails for the opening festivities of Parents Weekend. As the parents stay out way past their bedtimes, their kids - five residents of Campisi Hall - never show up at dinner. At first, everyone thinks that they're just being college students, irresponsibly forgetting about the gathering or skipping out to go to a party. But as the hours click by and another night falls with not so much as a text from the students, panic ensues. Soon, the campus police call in reinforcements. Search parties are formed. Reporters swarm the small enclave. Rumors swirl and questions arise. Libby, Blane, Mark, Felix, and Stella - The Five, as the podcasters, bloggers, and TikTok sleuths call them - come from five very different families. What led them out on that fateful night? Could it be the sins of their mothers and fathers come to cause them peril or a threat to the friend group from within? Told through multiple points of view in past and present - and marking the return of FBI Special Agent Sarah Keller from Every Last Fear and The Night Shift - Parents Weekend explores the weight of expectation, family dysfunction, and those exhilarating first days we all remember in the dorms when our friends become our family"--